THE TYPES OF ICT IN EFL CLASSROOM: CONSTRUCTIVE COMMUNICATIVE AND COLLABORATIVE TOOLS OF URBAN VOCATIONAL HIGH SCHOOL IN MAJALENGKA - Reza Octaviana Pratama; Raynesa Noor Emiliasari; Eva Fitriani Syarifah (English Education and Applied Linguistics Journal (EEAL Journal), 2020)
The types of ICT in education helped the education system to be better and directed. In 4.0 eras, English teachers are demanded to embrace technological change to be applied in the classroom during the teachinglearning process. In the preliminary study, the researcher found that the types of technology in EFL classroom posed its own tools that used by the teachers and the students in applying ICT itself. Thus, by this study aims to reveal the types of ICT implementation in urban vocational high schools. By using a qualitative case study design, the results of the study showed that types of ICTs’ tool changed the teaching-learning process more creative. The researcher observed the urban vocational high school, and then interviewed 1 English teacher, and 3 students which data presented in a tabular form. In this study, showed the types of ICT’s tool that has been implemented in urban vocational high school are constructive and collaborative tool. Eventually, the implementation types of ICT are expected to have a positive effect for the English teachers and also the students.